Simultaneous disturbance compensation and Hi/H[infinity] optimization in fault detection of UAVs - Liu, Hai; Zhong, Maiying; Yang, Rui (Zielona Góra: Uniwersytet Zielonogórski)
This paper deals with the problem of robust fault detection (FD) for an unmanned aerial vehicle (UAV) flight control system (FCS). A nonlinear model to describe the UAV longitudinal motions is introduced, in which multiple sources of disturbances include wind effects, modeling errors and sensor noises are classified into groups. Then the FD problem is formulated as fault detection filter (FDF) design for a kind of nonlinear discrete time varying systems subject to multiple disturbances.
Keywords: fault detection(FD); Hi/H[infinity] optimization; disturbance compensation; unmanned aerial vehicle (UAV)